The identification of trans-acting factors that regulate the expression of GDF5 via the osteoarthritis susceptibility SNP rs143383. - Catherine M Syddall (Public Library of Science (PLoS), 2013)
rs143383 is a C to T transition SNP located in the 5'untranslated region (5'UTR) of the growth differentiation factor 5 gene GDF5. The T allele of the SNP is associated with increased risk of osteoarthritis (OA) in Europeans and in Asians. This susceptibility is mediated by the T allele producing less GDF5 transcript relative to the C allele, a phenomenon known as differential allelic expression (DAE). The aim of this study was to identify trans-acting factors that bind to rs143383 and which regulate this GDF5 DAE. Protein binding to the gene was investigated by two experimental approaches: 1) competition and supershift electrophoretic mobility shift assays (EMSAs) and 2) an oligonucleotide pull down assay followed by quantitative mass spectrometry. Binding was then confirmed in vivo by chromatin immunoprecipitation (ChIP), and the functional effects of candidate proteins investigated by RNA interference (RNAi) and over expression. Using these approaches the trans-acting factors Sp1, Sp3, P15, and DEAF-1 were identified as interacting with the GDF5 5'UTR. Knockdown and over expression of the factors demonstrated that Sp1, Sp3, and DEAF-1 are repressors of GDF5 expression. Depletion of DEAF-1 modulated the DAE of GDF5 and this differential allelic effect was confirmed following over expression, with the rs143383 T allele being repressed to a significantly greater extent than the rs143383 C allele. In combination, Sp1 and DEAF-1 had the greatest repressive activity. In conclusion, we have identified four trans-acting factors that are binding to GDF5, three of which are modulating GDF5 expression via the OA susceptibility locus rs143383.